Stabilizing resistive random access memory by constructing an oxygen reservoir with analyzed state distribution. Issue 46 (25th November 2020) - Lin, Chih-Yang; Zhou, Kuan-Ju; Chang, Ting-Chang; Sun, Li-Chuan; Tan, Yung-Fang; Wu, Chung-Wei; Yeh, Yu-Hsuan; Chen, Wen-Chung; Lin, Chun-Chu; Huang, Wei-Chen; Wu, Cheng-Hsien; Lin, Shih-Kai; et al.
Abstract : In this paper, the instability mechanism of resistive random access memory was investigated, and a technique was developed to stabilize the distribution of high resistance states and better concentrate the set voltage. Abstract : In this paper, the instability mechanism of resistive random access memory (RRAM) was investigated, and a technique was developed to stabilize the distribution of high resistance states (HRS) and better concentrate the set voltage. Due to the accumulation of oxygen, an interface-type switching characteristic was observed on the I – V curves beneath the filament-type switching behavior. In this work, the interface-type switching characteristic is used to fit the natural distribution of HRS as an analysis of the instability mechanism. According to the results, the HRS distribution is attributed to the accumulation of excess oxygen ions left from the lower oxygen content and oxygen vacancy recombination during the reset process. The proposed solution with simple plasma treatment, can create an excess oxygen reservoir by changing the surface topography of the electrode to store the surplus oxygen ions from the reset process, eliminating the oxygen accumulation effect and further improving the device stability.